Peningkatan Pengetahuan Mahasiswa dalam Pembuatan Media Promosi Kesehatan Berbasis Digital di Program Studi Keperawatan Universitas Timor - Karol Octrisdey; Handrianus Akoit; Melkianus Ratu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The development of science and technology is increasingly rapid along with globalization and changes that are always happening in the world today. The development of science and technology also has a significant impact on the world of education, especially in the health sector, one of which is the community, which of course will get access to health services. In conveying health information messages to the community, of course, it will be more interesting and have a wide reach if you use digital media to design and create an attractive appearance to look at. This is because the development of digital technology has caused many people to utilize modern technology because of the importance of information in the digital era. This study aims to Increase Student Knowledge in Making Digital-Based Health Promotion Media in the Nursing Study Program at Timor University. This type of research is pre-experimental research with a One-Group Pretest-Posttest Design (One Group Pretest-Posttest). The sample in this study were 29 patients. Respondents will be given training in using the Canva application in making health promotion media, then their knowledge before and after regarding the Canva application and its use in making health promotion media will be measured. The results of the study showed that the average respondent had a pre-test score of 62.24 and the average respondent after being given training was 83.28. The results of the Kolmogorov-Smirnov test showed that the data was normally distributed with a p value> 0.05. Furthermore, in the Difference Test using the Paired Sample T-Test, a p value of 0.000 <0.05 was obtained. This shows that there is a difference in the knowledge of respondents before and after being given training related to the Canva application and its use in creating health promotion media. The conclusion is that providing training to increase respondent knowledge is very important to do so that the world of education is able to produce a generation that is always able to adapt to the development of science and technology that occurs.